Synthesis, Characterization and Antibacterial Activity of Metal Complexes of N-(1-piperidinobenzyl)nicotinamide - Raman, N.; Ravichandran, S. (Asian Journal of Chemistry, 2010)
Solid complexes of a new Mannich base N-(1-piperidino benzyl)nicotinamide (PBN) with Cu(II),Co (II), Ni(II) and Zn(II) complexes have been synthesized and characterized by spectral studies, molar conductance, magnetic susceptibility and elemental analyses. The antibacterial activity of the complexes has also been sudied.